Efeitos da falência sobre a arbitragem - Patricia Cabral Bittencourt (2016)
This study is dedicated to the effects of the interaction between arbitration and insolvency proceedings, according to brazilian legislation, doctrine and jurisprudence. Considering the current context of global economic crisis, the trend is to increase the declaration of insolvency, which combined with the increment of arbitration as business dispute resolution method, the interaction between the two institutes will raise, justifying the study of the effects of such contact. Initially, the principles of arbitration and insolvency are presented, demonstrating the compatibility between such systems. From there, the effects of the insolvency declaration on arbitration agreements, arbitration proceedings and arbitration award are analised, including their means of appeal, as well as the possibility of arbitration agreement concluded after the declaration of insolvency. Given the absolute legislative omission in Brazil on the issue the study proposes guidelines for the treatment of such matter, particularly from the verification of foreign laws and precedents.